Pengaruh Talent Management Dan Pengembangan Karier Terhadap Kinerja Pegawai Bappeda Kabupaten Simeulue - Santika, Arly (PT. Karya Inovatif Nusantara, 2025)
The company planning proces requires quality employee performance through the implementation of effective and comprehensive strategies so that company goals can be achieved successfully. To achieve this, talent management and career developmet are nedeed to improve employee performance. This research aims to ideentify and analyze the influence of talent management and career development on employee performance in the Bappeda of Simeulue Regency. This research uses a quantitative descriptive approach where the data used os in the form of numbers. Data collection was carried out using a questionnaire with a likert scale of 1 to 5 which was filled in by employee who had been identified as informans. The research location was at Bappeda Simeulue Regency.With a total 88 respondents for 6 months. The sampling technique used is the saturated sampling method , namely taking samples from the intire populaion. The data analysis method used is multiple linier regression analysis using SPSS 20 sofware. Based on the results of the analysis, it is proven that talent management has a positive and significant effect on employee performanc and career development has a positive and significant effect on employee performance.